Orientation distributions for cytochrome c on polar and nonpolar interfaces by total internal reflection fluorescence. - Tronin, Andrey (2002)
The formation of chemisorbed monolayers of yeast cytochrome c on both uncharged polar and nonpolar soft surfaces of organic self-assembled monolayers (SAM) on solid inorganic substrates was followed in situ by polarized total internal reflection fluorescence. Two types of nonpolar surfaces and one type of uncharged polar surface were used. The first type of nonpolar surface contained only thiol endgroups, while the other was composed of a mixture of thiol and methyl endgroups. The uncharged polar surface was provided by the mixture of thiol and hydroxyl endgroups. The thiol endgroups were used to form a covalent disulfide bond with the unique surface-exposed cysteine residue 102 of the protein. The mean tilt angle of the protein's zinc-substituted porphyrin was found to be 41 degrees and 50 degrees for the adsorption onto the nonpolar and uncharged polar surfaces, respectively. The distribution widths for the pure thiol and the thiol/methyl and thiol/hydroxyl mixtures were 9 degrees, 1 degrees, and 18 degrees, respectively. The high degree of the orientational order and good stability achieved for the protein monolayer on the mixed thiol/methyl endgroup SAM makes this system very attractive for studies of both intramolecular and intermolecular electron transfer processes.